Causes of fertility decline in India and Bangladesh: role of community - Dev, S. Mahendra; Sen, Binayak; James, K.S. (2002)
Conventional approaches to studies on fertility decline have long assumed the primacy of the household as the prime decision-maker. Aspects of the household such as its economic standard of living, social standing, exposure to mass media, work status were some of the influential factors at work on a couple's decision on their number of children. However, individual and household level factors have been unable in several instances to explain the full course of fertility transition seen in some Indian states and Bangladesh, where in some regions fertility transition cuts across socio-economic and cultural boundaries. Gaps in understanding such trends have been as this paper suggests due to the conventional emphasis on household level variables. It argues instead for the need to look at the influence the community plays in South Asia and to understand the levels of interaction that exist at household level and at the community level. - Reproduced.
Keywords: Fertility - Bangladesh; Fertility - India; Fertility